Chemoradiotherapy Is Superior to Radiotherapy Alone in Esophageal Cancer Patients Older Than 65 Years: A Propensity Score-Matched Analysis of the SEER Database - Xia, Xiaojie; Gao, Qing; Ge, Xiaolin; Liu, Zeyuan; Di, Xiaoke; Sun, Xinchen; Yang, Yan (Frontiers in Oncology, 2021)
Introduction: Radiotherapy (RT) is the main treatment for unoperated esophageal cancer (EC) patients. It is controversial whether adding chemotherapy (CT) to RT is beneficial for elderly EC patients. The purpose of our study was to compare the efficacy of chemoradiotherapy (CRT) with RT alone for non-surgical elderly esophageal cancer patients. Methods: 7101 eligible EC patients older than 65 years diagnosed between 2000 and 2018 were collected from the SEER database. All the samples were divided into the radiotherapy group and the chemoradiotherapy group. After being matched by propensity score matching (PSM) at a 1:1 ratio, 3020 patients were included in our analysis. The Kaplan-Meier method and log-rank test were applied to compare overall survival (OS) and cancer-specific survival (CSS). Results: After PSM, the clinical characteristics of patients between the RT and CRT groups were comparable. For EC patients older than 65 years, the 3-year OS and CSS in the CRT group were 21.8%, 27.4%, and the 5-year OS and CSS in the CRT group were 12.7%, 19.8%. The 3-year OS and CSS in the RT group were 6.4%, 10.4%, and the 5-year OS and CSS in the RT group were 3.5%, 7.2%, respectively. Next, these patients were divided into five subgroups based on the age stratification (age 65-69;70-74;75-79;80-84;>=85). In each subgroup analysis, the 3, 5-year OS and CSS showed significant benefit in the CRT group rather than in the RT group (all p<0.05). We were unable to assess toxicities between the two groups due to a lack of correlated information. Conclusions: CRT could improve OS and CSS for non-surgical EC patients older than 65 years. Adding chemotherapy to radiation showed a significant prognostic advantage for elderly esophageal cancer patients.